2010
DOI: 10.1007/s10272-010-0340-9
|View full text |Cite
|
Sign up to set email alerts
|

Boom and bust in the Baltic countries — Lessons to be learnt

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…4 For a discussion of the credit boom in CEE countries seeBakker and Gulde-Wolf (2010). A Baltic-specific analysis is provided byMartin and Zauchinger, 2009.…”
mentioning
confidence: 99%
“…4 For a discussion of the credit boom in CEE countries seeBakker and Gulde-Wolf (2010). A Baltic-specific analysis is provided byMartin and Zauchinger, 2009.…”
mentioning
confidence: 99%
“…Using ex-post cost of equity across all industry sectors in the Baltic countries, Mongrut, Paškevičius, Dubinskas, Kovalevskaja and Fuenzalida (2010) demonstrated that the cost of equity increased during the period 2005–2007, signalling that the Baltic country capital market was not conducive from a financing point of view. The Baltic countries experienced strong real GDP growth between the years 2000 and 2007 but post-2006–2007, the Baltics spiralled into recession (Martin, 2010). During the boom period, the real estate market in the Baltics was very expensive with the annual rate of bank lending rate being about 30–60 per cent, but ex-post real interest rates were close to zero or negative (accounting for deflation) and this led to rapid increase in credit growth by 2008 (Martin, 2010).…”
Section: Business Landscape In Baltic Countriesmentioning
confidence: 99%
“…The Baltic countries experienced strong real GDP growth between the years 2000 and 2007 but post-2006–2007, the Baltics spiralled into recession (Martin, 2010). During the boom period, the real estate market in the Baltics was very expensive with the annual rate of bank lending rate being about 30–60 per cent, but ex-post real interest rates were close to zero or negative (accounting for deflation) and this led to rapid increase in credit growth by 2008 (Martin, 2010). The study by Kenourgios and Samitas (2007) indicated that bank credit played an important role in fuelling economic development.…”
Section: Business Landscape In Baltic Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the capital markets, external financing continued to decline, with total gross capital inflows (syndicated bank lending, bond issuance, and equity initial public offerings) plummeting from $56. 6 Second, although government debt was negligible in 2008, the private sector had accumulated a substantial volume of short-term debt -in part because the policy of controlled appreciation of the ruble contributed to excessive foreign currency borrowing.26 Given that private capital inflows were mostly in the form of loans to firms and commercial banks, many of the commercial banks were heavily indebted, as they had borrowed from abroad at low interest rates. Therefore, even as the Russian government (in particular, Gazprom, the state-owned gas monopoly) was accumulating an impressive volume of foreign exchange, both state-owned corporations and private companies (in particular, the big-four of Gazprom, Rosneft, LUKoil, and Rostekhnologii) and banks were borrowing lavishly from abroad because dollar interest rates were much lower than ruble rates.27…”
Section: Russia Is Not Like the Rest Of Eastern Europementioning
confidence: 99%